2022
DOI: 10.1111/jeb.14066
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental drivers of colour and pattern in the Australian jacky dragon (Amphibolurus muricatus)

Abstract: The underlying drivers of variation in the colouration (colour and pattern) of animals can be genetic, non‐genetic, or more likely, a combination of both. Understanding the role of heritable genetic elements, as well as non‐genetic factors such as age, habitat or temperature, in shaping colouration can provide insight into the evolution and function of these traits, as well as the speed of response to changing environments. This project examined the genetic and non‐genetic drivers of continuous variation in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Overall, factors such as the vegetation structure and presence of predators seem to influence the signaling behavior of a population (Barquero, 2014; Ramos & Peters, 2017). Although the species relies on its cryptic coloration to avoid predators (Raynal et al, 2022), the visual displays have shown to be highly conspicuous (Woo, 2021). The signaling behavior of the species has been extensively studied and distinctive aggressive and submissive displays have been identified (Carpenter et al, 1970; Peters & Ord, 2003; Watt & Joss, 2003; Van Dyk & Evans, 2007; Barquero et al, 2015; Ramos & Peters, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, factors such as the vegetation structure and presence of predators seem to influence the signaling behavior of a population (Barquero, 2014; Ramos & Peters, 2017). Although the species relies on its cryptic coloration to avoid predators (Raynal et al, 2022), the visual displays have shown to be highly conspicuous (Woo, 2021). The signaling behavior of the species has been extensively studied and distinctive aggressive and submissive displays have been identified (Carpenter et al, 1970; Peters & Ord, 2003; Watt & Joss, 2003; Van Dyk & Evans, 2007; Barquero et al, 2015; Ramos & Peters, 2017).…”
Section: Introductionmentioning
confidence: 99%